Marketing management and strategy - Doyle, Peter, 1943-2003.; Stern, Philip, 1954- (Harlow, England ; New York : Financial Times Prentice Hall, 2006)
This text brings managers the latest ideas on branding, marketing and strategic change. It includes a step-by-step guide to developing marketing strategies and advice on pricing decisions, advertising and communications plans.
Ch. 1. Management : objectives and tasks -- Ch. 2. The customer-led business -- Ch. 3. Segmentation, positioning and the marketing mix -- Ch. 4. Strategic market planning -- Ch. 5. Market dynamics and competitive strategy -- Ch. 6. Building successful brands -- Ch. 7. Innovation and new product development -- Ch. 8. Pricing policy : delivering value -- Ch. 9. Communications strategy -- Ch. 10. Managing personal selling -- Ch. 11. Managing marketing channels -- Ch. 12. Marketing in service business -- Ch. 13. Turnaround management -- Ch. 14. Marketing in the future.
Includes bibliographical references (pages 427-434) and indexes.
Keywords: Marketing